1987
DOI: 10.1007/bf03007679
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-dose fentanyl on human median nerve somatosensory-evoked responses

Abstract: Median nerve somatoaensory evoked responses (MnSSERs) were recorded in nine neurologically normal adult cardiac patients before and during the administration of high-dose fentanyl. MnSSERs were recorded prior to induction and at r = 20rain and t = 45 rain postinduction. Fentanyl was administered as a slow bolus , followed by a continuous infusion at [10][11][12][13][14][15][16][17][18][19][20] From the Uniformed Services University of The Health Sciences, Naval Hospital, Bethesda, MD (AS) and the University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In theory, under normal conditions, the time difference is zero since no latency change should occur in the EPs observed. However, latency changes become nonzero when the neurological system condition changes (e.g., subject to change of depth of anaesthesia) (3)(4)(5)(6). Although there are many methods for extracting EPs from background EEGs, the most practical and popular method is still ensemble averaging (33,34) in which tens or hundreds of responses are averaged.…”
Section: The Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In theory, under normal conditions, the time difference is zero since no latency change should occur in the EPs observed. However, latency changes become nonzero when the neurological system condition changes (e.g., subject to change of depth of anaesthesia) (3)(4)(5)(6). Although there are many methods for extracting EPs from background EEGs, the most practical and popular method is still ensemble averaging (33,34) in which tens or hundreds of responses are averaged.…”
Section: The Methodologymentioning
confidence: 99%
“…[4], h(n) is a low-pass filter, and g(n) is the quadrature mirror filter (QMF). The coefficients of both filters are related to the wavelet function (t).…”
Section: Multiresolution Analysis Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…reproducible SSEPs can be recorded [94]. Recently Langeron et al [95] observed that fentanyl (induction dose 6 mg.kg À1 and maintenance dose 3 mg.kg…”
Section: Influence Of Anaesthetic Drugs On Sepsmentioning
confidence: 97%
“…Fentanyl causes dose-dependent increases in the latency of all waves, with cortical or late waves affected more than earlier waves, and decreases in amplitude. The changes in amplitude are more variable than the increases in latency [93,94]. Even at high doses of fentanyl (up to 60 mg.kg À1 )…”
Section: Influence Of Anaesthetic Drugs On Sepsmentioning
confidence: 99%